Rethinking academic performance metrics: beyond the publication craze / Ahlam Sundus - Sundus, Ahlam (Faculty of Pharmacy, 2024)
In the fast-paced world of academia, the metrics for success have become remarkably narrow. Universities worldwide have heavily relied on a primary benchmark to gauge their performance: the number of publications in indexed journals. It's a system that, on the surface, appears to encourage scholarly output but hides a deeper and more troubling truth – the ineffective implications of this fixation on publications as key performance indicators.